Secondary Hyperparathyroidism and Bone Turnover in Elderly with Bone Loss - Original Investigation - Nurdan Peker; Demet Tekdöş; Metin Erbil; Betül Kaya; Çağlayan Dere (Galenos Yayinevi, 2006)
Bone loss is common in the elderly. Parathyroid hormone (PTH), which regulates serum calcium levels,calcitonin and vitamin D metabolites have various effects on skeletal system. The aim of this study was to assess secondary hyperparathyroidism (HPTH) and bone turnover in elderly with bone loss. Fifty-five patients (9 men,46 women) older than 65 years with bone loss were included in the study. Bone mineral density was measured by dual energy x-ray absorptiomety (DXA) at L1-4 vertebrae and proximal femur regions. Patients with T scores <-1.5 at one of the measurement sites were included in the study. Study subjects were assessed in terms of fracture history, sunbathing and walking activity. Routine biochemical tests, serum osteocalcin (OC) and C-telopeptide type 1 collagen (CTX) and lateral thoracal and lumbar vertebrae radyographic evaluation was performed. Our results showed that 70.9% of the patients had HPTH. Total femur BMD values and femur neck T scores were significantly lower in HPTH group than PTH normal one (p=0.05, p=0.03). Serum OC and CTX levels were higher in both groups. There was a negative correlation with femur neck BMD and CTX (r=0,321). There was no correlation between serum PTH levels and lumbar vertebrae and proximal femur BMD values. Serum PTH and alkaline phosphatase levels showed a significant positive correlation. In conclusion secondary HPTH and increased bone turnover is common elderly with bone loss. Adequate calcium and vitamin D intake is important the older people. (Osteoporoz Dünyasından 2006; 12: 70-3)